Poly(ethylene glycol)-poly(ε-caprolactone)-based micelles for solubilization and tumor-targeted delivery of silibinin - Hassankhani Rad, Ashkan (Bioimpacts, 2020)
[Image: see text] Introduction: Silibinin is a naturally occurring compound with known positive impacts on prevention and treatment of many types of human illnesses in general and cancer in particular. Silibinin is poorly water soluble which results in its insufficient bioavailability and lack of therapeutic efficacy in cancer. Here, we proposed to examine the potential of micelles composed of poly(ethylene glycol) (PEG) as the hydrophilic block and poly(ε-caprolactone) (PCL), poly(α-benzylcarboxylate-ε-caprolactone) (PBCL), or poly(lactide)-(PBCL) (PLA-PBCL) as hydrophobic blocks for enhancing the water solubility of silibinin and its targeted delivery to tumor. Methods: Co-solvent evaporation method was used to incorporate silibinin into PEG-PCL based micelles. Drug release profiles were assessed using dialysis bag method. MTT assay also was used to analyze functional activity of drug delivery in B16 melanoma cells. Results: Silibinin encapsulated micelles were shown to be less than 60 nm in size. Among different structures under study, the one with PEG-PBCL could incorporate silibinin with the highest encapsulation efficiency being 95.5%, on average. PEG-PBCL micelles could solubilize 1 mg silibinin in 1 mL water while the soluble amount of silibinin was found to be 0.092 mg/mL in the absence of polymeric micelles. PEG-PBCL micelles provided the sustained release of silibinin indicated with less than 30% release of silibinin within 24 hours. Silibinin encapsulated in PEG-PBCL micelles resulted in growth inhibitory effect in B16 cancer cells which was significantly higher than what observed with free drug. Conclusion: Our findings showed that PEG-PBCL micellar nanocarriers can be a useful vehicle for solubilization and targeted delivery of silibinin.